Factors Affecting the Financial Resilience of Investors in the Capital Market Sector: Case Study on PT Telkom Indonesia Tbk - Sihaloho, Yolanda Maghdalena; Sabrina, Celine Amanda Sarifatul; Pandin, Maria Yovita R. (Neraca Keuangan : Jurnal Ilmiah Akuntansi dan Keuangan, 2025)
This study aims to analyze various factors that affect the financial resilience of investors in the capital market sector, with a focus on PT Telkom Indonesia Tbk. In a fluctuating capital market environment, investors are faced with risks such as stock price volatility, dividend policy, and company financial condition. This study uses data from PT Telkom's annual reports for the last five years and quantitative methods with analysis using SmartPLS 4. The results show that dividend policy has no significant effect on investors' financial resilience, while company liquidity has a significant positive effect. On the other hand, stock price volatility has a significant negative impact on investors' financial resilience. This study concludes that strong liquidity and good volatility management are essential in maintaining investors' financial stability.